Pengaruh Tayangan Bikin Laper Terhadap Minat Beli Makanan Generasi Z - Reza Aprila; Sigit Pramono Hadi (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
The problem in this study is that people's culinary purchasing interest is increasingly varied, no longer just a food item but has become a lifestyle to seek out various culinary delights. Television is one of the media that provides information about culinary tourism, one of which is the Bikin Laper program. However, Generation Z currently enjoys social media more than watching television. This study aims to determine the effect of the culinary program Bikin Laper on food purchasing interest in Generation Z. To analyze this problem, the theory used is the S-O-R theory with the research method used is a quantitative method with an explanatory type, which places the Bikin Laper program as the independent variable and food purchasing interest as the dependent variable. The study population includes Generation Z individuals aged 17–28 years and have watched Bikin Laper in the last three months. The sampling technique used purposive sampling with a total of 100 respondents. Data collection was carried out through an online questionnaire. Data analysis used hypothesis testing (t-test), simple linear regression and coefficient of determination with the help of SPSS version 26. The results of the study showed that the Bikin Laper program had a significant effect on Generation Z's food purchasing interest in the moderate category. These findings indicate that the higher the duration, frequency, and attention spent watching Bikin Laper, the higher the interest in purchasing culinary delights among Generation Z.